Evaluation of The Policy Implementation of The Appointment of Honorary Teachers to Become State Civil Servants with Work Agreements in Jember District - Muhamad Nur Purnamasidi; Ika Sisbintari; Eddy Wahyudi (Eduvest - Journal of Universal Studies, 2024)
Government Minister No. 49 of 2018 concerning the Management of Government Employees with Work Agreements (GEWA) explained that government agencies must arrange the needs of the number and type of GEWA positions based on position analysis and workload. problems with the availability of teachers in Jember Regency, especially at SMA/SMK, include a growing number of honorary teachers because many have opened their retirement period, honorary teachers are uneven and there are still non-linear in submitting study offers, supplements, and education. The Jember Regency Government has prepared 26% of the formation for Teachers in the Implementation of Appointment of Civil Servants of GEWA that is adjusted to the employee burden of 30% of the APBD. Data from BKSDM of Jember Regency recorded that the number of honorary teachers for elementary to high school/high school levels in the sub-district was around 2,787 people. and is not comparable to the 26% quota of teacher formations in the education district of Civil Servant PPK Students in Indonesia. Research results show that unsuitable and unfulfilled include effectiveness, efficiency, adequacy and equalization. Meanwhile, the other 2 dimensions including responsiveness and accuracy are appropriate and fulfilled.